LAW-DETERMINATION AS GROUNDING: A COMMON GROUNDING FRAMEWORK FOR JURISPRUDENCE. (26th February 2019) - Chilovi, Samuele; Pavlakos, George
ABSTRACT: Law being a derivative feature of reality, it exists in virtue of more fundamental things, upon which it depends. This raises the question of what is the relation of dependence that holds between law and its more basic determinants. The primary aim of this paper is to argue that grounding is that relation. We first make a positive case for this claim, and then we defend it from the potential objection that the relevant relation is rather rational determination. 1 Against this challenge, we argue that the apparent objection is really no objection, for on its best understanding, rational determination turns out to actually be grounding. Finally, we clarify the framework for theories on law-determination that results from embracing our view; by way of illustration, we offer a ground-theoretic interpretation of Hartian positivism and show how it can defuse an influential challenge to simple positivist accounts of law.